Трансформация программ с аффинным доступом к данным - Смирнов, А.Д.; Чемерис, А.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
The basic approaches of parallelization and optimization software for high-level languages are examined. Analyzed access to the data arrays whose indices are linear expressions of the indexes of cycles. Provided advantages and drawbacks of methods that are generally used in software.